Method for continuously producing biodegradable fibrous material containing inorganic filler particles by wet spinning method, and batt-like bone regeneration material produced by said method

The wet spinning method sprays spinning raw liquid in poor solvents with different solubility, solving the problems of high cost and complex processes of electrospinning, and achieving efficient and low-cost biodegradable fiber spinning production, fiber shape and Improved cell adhesion.

CN119256126APending Publication Date: 2025-01-03NAGOYA INSTITUTE OF TECHNOLOGY +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380042342.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-23
Filing Date
2023-05-22
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing electrospinning process is used to manufacture biodegradable fiber spinning containing a large number of inorganic filler particles, and it is difficult to maintain the fiber shape. It requires complex processes such as kneading and high voltage processing, resulting in manufacturing costs and efficiency. Low.

Method used

By using wet spinning method, the spinning raw liquid is prepared by stirring inorganic filler particles and biodegradable resin in a good solvent, and sprayed into poor solvents with different solubility in a wet spinning device in fibers, using its own weight and Solvent diffusion and curing are performed to avoid blockage of spinning stock liquid and high voltage treatment.

Benefits of technology

The biodegradable fiber spinning containing a large number of inorganic filler particles is achieved efficiently and at low cost. The fibrosis process is stable, the fiber shape is maintained well, the manufacturing cost is reduced, and the cell adhesion and antibacterial properties of the fibers are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119256126A_ABST
    Figure CN119256126A_ABST
Patent Text Reader

Abstract

A method for producing a biodegradable fiber containing inorganic filler particles by a wet spinning method, said method comprising: dissolving a mixture, which is obtained by mixing inorganic filler particles and a biodegradable resin at a weight ratio of 50-80: 50-20, in a good solvent, and stirring the mixture to prepare a spinning solution; a spinning tube of a wet spinning device is filled with the spinning solution, and the spinning solution is pressed downwards from a discharge port of an incidence needle and is ejected into a collection container. In the collecting container, the upper layer and the lower layer are filled with a first poor solvent with the solubility parameter value having a small deviation degree relative to the good solvent and a second poor solvent with the specific gravity larger than that of the first poor solvent and the solubility parameter value having a large deviation degree relative to the good solvent. The spinning solution pressed out from the ejection opening of the injection needle is injected into the first poor solvent in the collection container in a fiber shape by means of self weight, and then is continuously injected into the second poor solvent filled with the first poor solvent. The fibrous spinning solution entering the second poor solvent is formed into continuous long fibers and floats and accumulates at the bottom of the collection container, thereby forming a cotton fiber shape.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for continuously producing a biodegradable fiber material containing inorganic filler particles by wet spinning, and a cotton-like bone regeneration material produced by the method. The present invention also relates to a method for producing a nonwoven fabric composed of biodegradable fibers containing inorganic fillers by wet spinning. Background Art

[0002] In the field of bone regeneration medicine, polylactic acid is used as a matrix and is compounded with calcium salt particles (β-tricalcium phosphate, silicon-dissolved calcium carbonate, hydroxyapatite, etc.), and the material formed by electrostatic spinning (ES) is used as a bone regeneration material. Bone regeneration materials are generally used in block or granular form. The bone regeneration material composed of biodegradable fibers spun by this method has the excellent characteristics of good formability during surgery and can solve the concerns of moving and falling off from the target site. The inventors of the present invention successfully achieved cotton-like formation by receiving the biodegradable fibers ejected from the nozzle using ES with a collection container filled with ethanol, and recovering and drying the fibers floating in the ethanol solution (US8853298). Cotton-like bone regeneration materials can easily cope with any shape of the affected part during surgery, so they are excellent materials clinically.

[0003] As the matrix resin of biodegradable fiber, PLGA is used in addition to polylactic acid. PLGA is an excellent biodegradable resin with higher bioabsorbability than polylactic acid and recognized safety by FDA. Therefore, PLGA is recently used as a matrix to be compounded with calcium salt particles and fiberized by ES. PLGA is synthesized by copolymerization of lactic acid and glycolic acid, and the biodegradability can be controlled by adjusting the ratio of lactic acid to glycolic acid. Among PLGA (85:15) with 85% lactic acid: 15% glycolic acid and PLGA (75:25) with 75% lactic acid: 25% glycolic acid, PLGA (75:25) has higher decomposability. On the other hand, there are crystalline L-body and optical isomer, i.e. amorphous D-body, in the lactic acid of polylactic acid. PDLLA containing D-body is difficult to crystallize and easy to decompose than PLLA containing only L-body without D-body. Therefore, by copolymerizing PDLLA containing D-body with PGA, PDLLGA with much higher decomposability than PLGA (PLLGA) without D-body can be synthesized.

[0004] ES can contain inorganic filler particles that become bone formation factors in spinning solution to carry out fibrosis, so it is an excellent method as a method for manufacturing a bone regeneration material composed of biodegradable fibers. However, ES needs to be used for this special equipment, and the manufacturing cost is high. And, in order to spin by ES, inorganic particles need to be uniformly dispersed in the spinning solution, therefore, in order to spin the fiber containing a large amount of inorganic filler particles, it is necessary to carry out operations such as mixing in the manufacture of the spinning solution, which further improves the manufacturing cost. In addition, ES is a method for fibrosis in which the spinning solution applied with high voltage is ejected from a nozzle and its electric field is flown, therefore, if PDLLGA with low molecular weight is adopted, it is difficult to maintain fiber shape, and as a result, it is difficult to carry out the spinning of the biodegradable fibers adopting PDLLGA.

[0005] In addition to the cotton-like bone regeneration material, the inventors of the present invention have also developed a cell culture substrate using a non-woven fabric made of ES (U.S. Patent Nos. 6,602,999 and 6,639,035), and have found that the inorganic particles contained in the fibers of the non-woven fabric made of ES are exposed on the fiber surface and exhibit good cell adhesion, and can be used as an excellent three-dimensional cell culture substrate. However, it also has the same problems that arise with the use of ES. Prior art literature Patent Literature

[0006] Patent Document 1: U.S. Patent No. 8853298 Patent Document 2: U.S. Patent No. 6602999 Summary of the invention Technical problem to be solved by the invention

[0007] As a method for spinning biodegradable fibers containing inorganic filler particles, in addition to ES, wet spinning can also be used. Inorganic filler particles are added to a solution prepared by dissolving a biodegradable resin in a good solvent, stirred and dispersed to prepare a spinning solution, and the spinning solution prepared in this way is injected into a spinning tube and ejected from a nozzle so that the spinning solution is ejected in the form of fibers into a collection container filled with a poor solvent, thereby spinning composite biodegradable fibers containing inorganic filler particles in a poor solvent.

[0008] In the wet spinning method, the spinning solution ejected from the nozzle in a fibrous form is injected into a poor solvent so that the good solvent contained in the spinning solution is separated in the poor solvent to be fiberized. However, if the speed at which the good solvent penetrates into the poor solvent is too slow, the spinning solution ejected from the nozzle is difficult to be fiberized in the poor solvent. On the contrary, if the speed at which the good solvent penetrates into the poor solvent is too fast, the spinning solution will be clogged at the nozzle. In particular, when a large amount of inorganic particles are contained in the spinning solution, the spinning solution is easily clogged at the portion where the spinning solution is ejected from the narrow nozzle of the nozzle to the poor solvent. Solutions to technical problems

[0009] In order to solve the above technical problems and realize efficient wet spinning, the inventors of the present invention have repeatedly conducted in-depth research, and as a result, they have come up with a method of using two layers of two poor solvents with different solubilities in the collection container of the wet spinning device. That is, it was found that by extruding a spinning stock solution prepared by injecting a good solvent in an amount substantially equal to that of a sample (inorganic particles and biodegradable resin) from the nozzle outlet of the wet spinning device into the collection container, the spinning stock solution extruded from the nozzle outlet is incident in a fiber-like manner into a first poor solvent having a small difference in solubility parameter with the good solvent, and then the spinning stock solution incident in a fiber-like manner is incident into a second poor solvent having a larger difference in solubility parameter with the good solvent than that of the first poor solvent, so that fibers containing a large amount of inorganic particles can be spun.

[0010] Based on the above findings, the inventors of the present invention have completed the following invention: A method for producing biodegradable fibers containing inorganic filler particles by wet spinning, which is a method for producing biodegradable fibers containing inorganic filler particles by wet spinning, wherein: A mixture of inorganic filler particles and biodegradable resin in a weight ratio of 50-80:50-20 is placed in a mixing container. A good solvent having a predetermined amount relative to the mixture is added to the mixing container, and the biodegradable resin is dissolved in the good solvent and stirred, thereby preparing a spinning solution in which the inorganic filler particles are dispersed in the solution. The prepared spinning solution is filled into the spinning tube of the wet spinning device, The spinning solution filled in the spinning tube is extruded vertically downward from a nozzle of an incident needle having a specified diameter at a specified extrusion speed and ejected into a cylindrical collection container having a specified height, wherein the collection container is filled with a first poor solvent having a solubility parameter value with a first deviation relative to the good solvent and a second poor solvent having a specific gravity greater than that of the first poor solvent and a solubility parameter value with a second deviation greater than the first deviation relative to the good solvent, filling upper and lower layers, The spinning stock solution extruded from the nozzle outlet is incident into the first poor solvent in the collecting container in the form of fibers by its own weight, and the surface of the spinning stock solution incident into the liquid of the first poor solvent in the form of fibers is solidified by mutual diffusion of the detachment of the good solvent and the intrusion of the first poor solvent. Next, the surface-solidified fibrous spinning solution is continuously injected into the second poor solvent below the first poor solvent filling the collection container by its own weight. The fibrous spinning solution injected into the second poor solvent is further solidified and fiberized in the second poor solvent by mutual diffusion of the detachment of the good solvent and the intrusion of the second poor solvent into the interior of the spinning solution. The solidified fibers become continuous long fibers that are not bonded to each other in the second poor solvent and float and accumulate at the bottom of the collecting container. The fibers accumulated at the bottom of the collecting container are taken out from the collecting container and dried.

[0011] The inventors of the present invention have also completed the following inventions: A cotton-like bone regeneration material is produced by a wet spinning method, wherein the cotton-like bone regeneration material is produced by the following steps: A mixture of calcium salt particles and biodegradable resin in a weight ratio of 50-80:50-20 is placed in a mixing container. A good solvent having a predetermined amount relative to the mixture is added to the mixing container, and the biodegradable resin is dissolved in the good solvent and stirred, thereby preparing a spinning solution in which the calcium salt particles are dispersed in the solution. The prepared spinning solution is filled into the spinning tube of the wet spinning device, The spinning solution filled in the spinning tube is extruded vertically downward from a nozzle of an incident needle having a specified diameter at a specified extrusion speed and ejected into a cylindrical collection container having a specified height, wherein the collection container is filled with a first poor solvent having a solubility parameter value with a first deviation relative to the good solvent and a second poor solvent having a specific gravity greater than that of the first poor solvent and a solubility parameter value with a second deviation greater than the first deviation relative to the good solvent, filling upper and lower layers, The spinning stock solution extruded from the nozzle is incident in the first poor solvent in the collecting container in the form of fibers, and the surface of the spinning stock solution incident in the first poor solvent liquid in the form of fibers is solidified by mutual diffusion of the detachment of the good solvent and the intrusion of the first poor solvent. Next, the surface-solidified fibrous spinning solution is continuously injected into the second poor solvent below the first poor solvent filling the collection container. The fibrous spinning solution injected into the second poor solvent is further solidified and fiberized in the second poor solvent by mutual diffusion of the detachment of the good solvent and the intrusion of the second poor solvent into the interior of the spinning solution. The solidified fibers become continuous long fibers that are not bonded to each other in the second poor solvent and float and accumulate at the bottom of the collection container. The fibers accumulated at the bottom of the collection container are taken out from the collection container and dried.

[0012] The inventors of the present invention have also completed the following inventions: A wet spinning device for an improved wet spinning method, which is a wet spinning device for an improved wet spinning method, wherein the device comprises: A spinning tube into which a spinning solution is injected, wherein the spinning solution is prepared by adding 50-80 wt % of inorganic filler particles and 50-20 wt % of biodegradable resin into a mixing container, dissolving them in a good solvent, and stirring. a nozzle connected to the end of the spinning tube and having a spray outlet at the front end, and A cylindrical collecting container having a specified height; The collection container comprises: an injection section for injecting the spinning solution extruded from the nozzle outlet into the first poor solvent and passing the first poor solvent, a fiber solidification section adjacent to the ejection section, which allows the spinning solution passing through the ejection section to be injected into a second poor solvent having a larger specific gravity than the first poor solvent and a larger deviation of the solubility parameter value from the good solvent than the first poor solvent to be solidified; The fiber recovery section is adjacent to the fiber solidification section and is used to collect the solidified fibers passing through the fiber solidification section in the form of cotton wool and float on the bottom of the collection container. The fiber solidification section and the fiber recovery section are connected in a detachable manner. After the solidified fibers float and accumulate at the bottom of the fiber recovery section, the fiber recovery section is separated from the fiber solidification section, thereby being able to recover the fibers accumulated at the bottom of the collection container.

[0013] Preferably, the amount of the good solvent added to the mixture of the inorganic filler particles and the biodegradable resin is adjusted to an amount in which the inorganic filler particles do not settle in the solution but are uniformly diffused in the spinning tube, and can be fiberized in the poor solvent by extruding the spinning solution from the incident needle into the poor solvent.

[0014] Preferably, the particle size of the β-TCP particles is 0.4-5 μm.

[0015] Preferably, the spinning solution is prepared by dissolving acetone in an amount of 0.7 to 1.3 by weight ratio relative to a mixture 1 in which β-TCP particles having a particle size of 3 to 5 μm and PDLLGA resin are mixed in a weight ratio of 50-80:50-20.

[0016] Preferably, the spinning solution is prepared by dissolving acetone in an amount of 1.15 to 1.40 by weight ratio relative to a mixture 1 in which β-TCP particles having a particle size of 0.3 to 0.5 μm and PDLLGA resin are mixed in a weight ratio of 50-80:50-20.

[0017] Preferably, the position of the interface between the first poor solvent and the second poor solvent added to the collection container is set to a position close to the nozzle outlet. If the spinning solution ejected from the nozzle outlet of the incident needle passes through the first poor solvent having a small difference in solubility parameter with the good solvent for a long distance, the fiber injected from the nozzle outlet is easily torn off in the middle. Therefore, by making the height position of the interface between the first poor solvent and the second poor solvent close to the nozzle outlet, the incident fiber can be prevented from being torn off in the middle and can be accumulated as a continuous fiber at the bottom of the collection container.

[0018] Preferably, the inorganic filler particles are calcium phosphate particles, and more preferably β-TCP particles. In addition, β-TCP containing silver has antibacterial properties and is therefore advantageous.

[0019] Preferably, the height of the cylindrical collection container of the wet spinning device of the present invention is 50 to 100 cm, and it is divided into an ejection part, a fiber solidification part, and a fiber recovery part from top to bottom. The spinning stock solution extruded in the form of fibers from the nozzle outlet passes through the first poor solvent in the ejection part by its own weight, and then enters the second poor solvent in the fiber solidification part. After passing through the fiber solidification part, it is introduced into the fiber recovery part which is also filled with the second poor solvent, and floats and accumulates at the bottom of the collection container in the form of cotton wool. By separating the fiber recovery part of the collection container from the fiber solidification part, the cotton wool-like fibers accumulated at the bottom of the collection container are taken out from the collection container, recovered, and dried, so that a cotton wool-like bone regeneration material can be obtained.

[0020] Preferably, the good solvent is acetone, the first poor solvent is ethanol, and the second poor solvent is water.

[0021] Preferably, the good solvent is acetone, the first poor solvent is a mixed solution of acetone and water, and the second poor solvent is water.

[0022] Preferably, the good solvent is chloroform, the first poor solvent is ethanol, and the second poor solvent is water.

[0023] Preferably, pure water is used as the second poor solvent. If the total solvent (the good solvent, the first poor solvent, and the second poor solvent) contains chlorine, in the case of β-TCP containing silver, it may react with the silver contained therein to generate AgCl, so a chlorine-free solvent is preferred.

[0024] Preferably, the biodegradable fiber contains 50-80% by weight of inorganic filler particles, more preferably 60-70% by weight. The wet spinning method is to press out a spinning solution prepared by mixing a resin with filler particles and dissolving them with an organic solvent from a spinning tube, so that a spinning solution containing a large amount of inorganic filler particles can be easily prepared. In ES, a slurry with low viscosity is used during spinning, so the dispersibility of the inorganic filler particles must be greatly improved in advance, and a special process (such as mixing) is required to uniformly disperse a large amount of filler particles in the solution. However, in the wet spinning method, since a slurry with a higher viscosity than ES is used, it is not necessary to perform such a special process, and the particles can be dispersed in the solution by stirring. This is because the fluidity of the polymer solution between the landfill particles becomes low, which can prevent coagulation.

[0025] Preferably, the inorganic filler particles are calcium phosphate particles, more preferably β-TCP particles. When the biodegradable resin is decomposed by contact with body fluids, the β-TCP particles are eluted, and the β-TCP is dissolved, calcium ions and phosphorus ions are eluted, promoting bone formation by bone resorption and replacement.

[0026] Preferably, the β-TCP particles are β-TCP particles containing silver ions. As the β-TCP particles dissolved from the biodegradable fibers dissolve, the silver ions contained in the β-TCP particles are eluted and exhibit antimicrobial properties.

[0027] Preferably, the incident needle of the nozzle of the wet spinning device is 27G (inner diameter 0.19±0.02mm, outer diameter 0.41±0.01mm) or 22G (inner diameter 0.41±0.03mm, outer diameter 0.72±0.02mm), so that the outer diameter of the spun fiber is 80-200μm. More preferably, the injection needle of the nozzle of the wet spinning device is 27G, and the outer diameter of the spun fiber is 100-150μm. In another experiment conducted by the inventors, when 22G is used for the incident needle of the nozzle, good spinning can be performed at a resin concentration of 16.7-20.5% by weight and an extrusion speed of 3ml / h, but when the resin concentration is 15.3% by weight, the viscosity is low, and the inorganic particles are easy to settle in the spinning tube to become inhomogeneous fibers. When the resin concentration is 26.5% by weight, the viscosity is high and it is not easy to extrude. The fibers extruded with 22G are both coarse and brittle. On the other hand, when the nozzle diameter is 27G, the suitable resin concentration range becomes narrower, but good spinning is possible with a resin concentration of 20 wt% in the spinning solution and an extrusion speed of 3 ml / h. The fiber diameter is thinner and less brittle than when 22G is used, and a better fiber can be obtained as a product. Unlike the ES method, the wet spinning method simply squeezes out the spinning solution and ejects it from the nozzle. Therefore, the resin concentration of the spinning solution can be set relatively freely according to the ejection speed and the thickness of the fiber. However, the appropriate resin concentration of the spinning solution varies depending on the thickness of the nozzle.

[0028] Preferably, a metal or plastic net is sunk to the bottom of the fiber recovery section of the collection container so that the wet-spun fibers are deposited thereon. When the net is pulled up, the fibers are still soft and become non-woven or cotton-like. When the net is directly immersed in water, it maintains this state and solidifies.

[0029] Preferably, a winding device is provided at the bottom of the collection container, and the fibers accumulated after passing through the second poor solvent are wound by the winding device. By increasing the winding speed of the winding device, a nonwoven fabric with uniform fiber direction can be obtained. Effects of the Invention

[0030] In the present invention, the amounts of sample (inorganic particles and biodegradable resin) and good solvent are adjusted to amounts in which the sample particles do not settle but diffuse evenly in the good solvent, and in which the spinning stock solution extruded from the nozzle can be fiberized in the poor solvent, thereby enabling biodegradable fibers to be spun on a commercial basis using a wet spinning apparatus.

[0031] In the wet spinning method of the present invention, the spinning stock solution extruded in the form of fibers from the nozzle outlet into the poor solvent contains a large amount of inorganic particles (specific gravity of β-TCP is 3.14 g / cm 3), therefore, it settles downward in the poor solvent (the specific gravity of ethanol is about 0.8, and the specific gravity of water is 1) by its own weight of the spinning solution and passes through the first poor solvent and the second poor solvent in sequence. In the process of sedimentation, it gradually becomes fiberized and accumulates at the bottom of the collecting container, so that the accumulated fibers can be recovered.

[0032] The specific gravity of the second poor solvent filling the fiber solidification part of the collection container of the wet spinning method device of the present invention is greater than that of the first poor solvent filling the ejection part thereon, so that due to the difference in specific gravity, a double layer is formed in which the second poor solvent floats on the first poor solvent. Therefore, by ejecting the spinning solution from the nozzle of the device to the first poor solvent, the spinning solution ejected in the form of fibers can pass through the first poor solvent and the second poor solvent with different solubility parameters in sequence by its own weight, so that the spinning solution can be gradually solidified and fiberized in the process. However, in the case where ethanol is used as the first poor solvent and water is used as the second poor solvent, since ethanol is hydrophilic, if water is coordinated around the hydrophilic group after stirring, the water will surround the ethanol molecules and mix. Therefore, it is preferred to slowly inject ethanol on the water so that the water will not be coordinated around the hydrophilic group of ethanol, and a separated state will be produced by the difference in specific gravity.

[0033] In a preferred embodiment of the present invention, the second poor solvent (e.g., water) used for solidifying the spinning solution has a specific gravity greater than that of the good solvent (e.g., acetone), so the good solvent (e.g., acetone) separated from the fiber does not immediately float upward and is stored near the solidified fiber. As a result, the good solvent floats near the fiber after being separated from the fiber, and does not dissolve the fiber accumulated at the bottom of the collection container after solidification, so the accumulated fibers do not adhere to each other and can be recovered from the collection container in the form of cotton wool.

[0034] The biodegradable resin used in the present invention does not need to use a chlorine-based solvent (such as chloroform) with high solubility as a good solvent for preparing the spinning solution by selecting a resin with high solubility in the solvent, and a non-chlorine-based solvent (such as acetone) can be used.

[0035] The biodegradable fiber produced by the wet spinning method of one embodiment of the present invention has a long fiber length, and a substantially continuous fiber can be piled up into a cotton-like state for recovery. The cotton-like bone regeneration material thus piled up and recovered has a wider interval between fibers than cotton produced by ES, and has a wide micro-environment for cells to infiltrate between fibers and bond to each other for proliferation.

[0036] The biodegradable fiber produced by the wet spinning method of the present invention has fewer pores on the fiber surface than the fiber spun from ES, has a dense cross-sectional structure, and is excellent in shape retention.

[0037] The biodegradable fiber produced by the wet spinning method of the present invention has a flat cross-sectional shape and is excellent in cell adhesion.

[0038] The wet spinning method of the present invention is different from the ES method in that a physical force is applied to the spinning solution to force it out from the spinning tube to the nozzle, so the content of the filler particles in the spinning solution has a high degree of freedom. By containing 50% by weight, more preferably 60% by weight, and even more preferably 70% by weight of calcium phosphate, the particles form a concavo-convex structure on the fiber surface. The concavo-convex structure on the fiber surface is suitable for cell adhesion.

[0039] After the cotton-like bone regeneration material composed of PDLLGA resin fibers manufactured by the wet spinning method of the present invention is implanted in the body, PDLLGA dissolves in the body, the local pH value decreases, and an acidic environment is formed. As a result, β-TCP dissolves in the acidic environment, and trace amounts of calcium ions and phosphate ions are dissolved and slowly released, which helps promote bone formation.

[0040] When the biodegradable fiber produced by the wet spinning method of the present invention contains β-TCP particles containing silver ions as a filler, the biodegradable resin dissolves in the body, the pH value decreases, and the β-TCP filler dissolves in an acidic environment, resulting in the dissolution of the silver ions contained in the β-TCP particles to exert antibacterial properties. Thus, by combining the PDLLGA fiber produced by the wet spinning method of the present invention and the β-TCP particles containing silver ions, the antibacterial properties of the bone regeneration material can be exerted in the late postoperative period after implantation in the body.

[0041] In the wet spinning method of the present invention, acetone used as an organic solvent does not contain chlorine, so even if it comes into contact with silver, silver chloride will not be generated. As a result, the Ag ions contained in the β-TCP particles do not form AgCl, but exist as Ag ions, so the antibacterial properties of the Ag ions can be exerted. In addition, the particles will not turn black due to the generation of AgCl.

[0042] In the biodegradable fiber spun by the wet spinning method of the present invention, the inorganic particles contained therein are exposed on the fiber surface without being covered by the resin to form a concavo-convex shape, and therefore, when administered to the human body, excellent cell adhesion is exhibited. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a conceptual diagram showing a wet spinning method according to an embodiment of the present invention. Figure 2 This is a SEM photograph showing the shape of the biodegradable fiber spun by the wet spinning method (using acetone as the good solvent, ethanol as the first poor solvent, and water as the second poor solvent) according to one embodiment of the present invention. Figure 3This is a SEM photograph showing the uneven shape of the surface of the biodegradable fiber spun by the wet spinning method (using acetone as the good solvent, ethanol as the first poor solvent, and water as the second poor solvent) in the example of the present invention. Figure 4 This is a conceptual diagram showing the deviation of the Hansen solubility parameters of the solvents when acetone is used as the good solvent, ethanol is used as the first poor solvent, and water is used as the second poor solvent in the present invention. Figure 5 This is a conceptual diagram showing a wet spinning apparatus used in a wet spinning method (using acetone as a good solvent, ethanol as a first poor solvent, and water as a second poor solvent) according to an example of the present invention. DETAILED DESCRIPTION definition

[0044] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings. definition

[0045] <PLLGA resin> In the present invention, PLLGA resin refers to a PLGA resin synthesized by copolymerization of lactic acid and glycolic acid containing only L-forms. A polymerization ratio of PLLA to PGA of 85:15 is called PLLGA (85:15), and a polymerization ratio of PLLA to PGA of 75:25 is called PLLGA (75:25). PLLGA can improve decomposability by increasing the ratio of PGA. Chlorine-based solvents such as chloroform must be used to dissolve PLLGA with a solvent.

[0046] <PDLLGA resin> In the present invention, PDLLGA resin refers to a PLGA resin synthesized by copolymerization of lactic acid containing D-body and L-body and glycolic acid. Lactic acid used for synthesizing PLGA has crystalline L-body and optical isomer, i.e., amorphous D-body, and PLA has poly(L-lactic acid) (PLLA) consisting of only L-body and poly(D-lactic acid) (PDLLA) containing L-body and D-body. The polymerization ratio of PDLLA to PGA is 75:25, which is called PDLLGA (75:25). The copolymer of PDLLA and PGA, PDLLGA, has particularly high flexibility among PLGA. The degradability of PDLLGA can be controlled by changing the polymerization ratio of PDLLA to PGA. Although it is difficult to numerically determine the amount of D-body contained in PDLLGA, in the present invention, the amount of D-body contained in the PDLLGA resin is sufficient to have a decomposability that allows the resin to be dissolved in acetone by containing the D-body.

[0047] <Wet spinning method> In the present invention, wet spinning refers to a method of solidifying into a fiber form by interdiffusion of an organic solvent called a good solvent and an intrusion of a poor solvent. The selection of a good solvent and a poor solvent affects the solidification rate of the polymer and the interdiffusion of the solvent, and determines the fiber form with a balance of the speed of the interdiffusion. In a preferred embodiment of the wet spinning method of the present invention, the conditions for forming a cotton-like state by fiberization of a PDLLGA resin containing calcium phosphate particles and improvement are performed.

[0048] <Good solvent> The good solvent in the present invention refers to a solvent used to dissolve a mixture of biodegradable resin and calcium phosphate particles to prepare a spinning solution. Chlorine-based organic solvents such as chloroform are excellent in resin dissolving power, but are toxic. Acetone is inferior to chloroform in solubility, but does not contain chlorine and is therefore safe for organisms. The PDLLGA resin used in the present invention can use acetone, a highly safe non-chlorine-based solvent, instead of toxic chlorine-based organic solvents such as chloroform.

[0049] In the present invention, when preparing the spinning solution, when the particle size of the inorganic filler particles is about 4 μm, the amount of the good solvent is preferably an amount of 1:0.7 to 1.3 relative to the weight of the mixture of the inorganic filler particles and the biodegradable resin. More preferably, the ratio of the two is approximately 1:1. In the experiment conducted by the inventors of the present invention, if the weight ratio of the good solvent (acetone) to the sample (mixture of inorganic filler particles and biodegradable resin) is greater than 1.3, the particles are easily precipitated in the spinning tube, and the amount of inorganic particles (β-TCP) dispersed at the early and late stages of the ejection will change, and the product will become inhomogeneous. On the contrary, if the amount of the good solvent (acetone) is less than 0.7, it will be difficult to squeeze out from the nozzle outlet. When the amount of the good solvent (acetone) to the sample (mixture of β-TCP and PDLLGA resin) is in the range of a weight ratio of 1:0.7 to 1.3, the spinning solution can be squeezed out from the ejection outlet and fiberized in the poor solvent.

[0050] When the particle size of the inorganic filler particles is about 0.3 to 0.5 μm, the amount of the good solvent is preferably an amount of 1:1.15 to 1.40 relative to the weight of the mixture of the inorganic filler particles and the biodegradable resin. According to the experiment conducted by the present inventors using β-TCP particles with a particle size of 0.4 μm, if the amount of acetone is 1.1 relative to the sample 1 in a weight ratio, it is difficult to use a pump to press the spinning solution out of the spinning tube. On the contrary, if the amount of acetone is 1.45 relative to the sample 1 in a weight ratio, the β-TCP particles will settle and separate in the solution over time.

[0051] <Poor Solvent> In the present invention, a poor solvent refers to a solvent used in a coagulation bath as a solvent that does not dissolve the biodegradable resin. In chemistry, a poor solvent refers to a solvent that is a poor solvent for a specific substance-solvent system when the solute-solvent interaction (free energy) is less than the arithmetic mean of the solute-solute and solvent-solvent interactions. However, the poor solvent used in the method of the present invention is selected based on the solubility parameter as an indicator and the balance of mutual diffusion with the organic solvent. In the present invention, when PDLLGA is used as the biodegradable resin, ethanol or water that does not dissolve PDLLGA can be preferably used.

[0052] <Deviation of Hansen Solubility Parameter Value> The biodegradable resin, good solvent, and poor solvent used in the method of the present invention can be selected based on the deviation of the Hansen solubility parameter value. When the good solvent is acetone and the poor solvent is ethanol, the speed at which the spinning solution prepared by dissolving the biodegradable resin in the good solvent is extruded from the nozzle outlet in the form of fibers and solidified in the poor solvent is determined by the deviation of the Hansen solubility parameter value (vector value), and the Hansen solubility parameter value (vector value) is determined by the interaction of (i) polarizability, (ii) hydrogen bonding, and iii) dispersibility of acetone and ethanol. The Hansen solubility parameter value of the solute, i.e., the polymer, should be close to the solubility parameter value of the good solvent (e.g., acetone). The Hansen solubility parameter of ethanol at 25°C is 26.5δ[(MPa) 1 / 2 ]), the Hansen solubility parameter of acetone is 20.0[(MPa) 1 / 2 ]), the deviation between the two is 9.8[(MPa) 1 / 2 ](See Figure 4 ). Under this deviation, the spinning solution will not solidify rapidly at the front end of the nozzle, so the spinning solution extruded from the nozzle will not be blocked. However, since the Hansen solubility parameter value of ethanol is close to the Hansen solubility parameter value of acetone, there will be a certain degree of polymer dissolution, and the spinning solution extruded in the form of fibers cannot maintain the shape of the fibers during the sedimentation process in ethanol and is easily torn apart in the middle. Moreover, since the specific gravity of ethanol is roughly the same as that of acetone, the acetone separated from the spinning fibers in ethanol will play a role in dissolving the spinning fibers near the fibers, so there is a problem of hindering the fiberization of the spinning solution.

[0053] When acetone is used as a good solvent to prepare a spinning solution and water is used as a poor solvent to extrude the spinning solution from a nozzle into the poor solvent in the form of fibers, the Hansen solubility parameter of water is 47.8 δ [(MPa) 1 / 2 ], the Hansen solubility parameter of acetone is 20.0δ[(MPa) 1 / 2 ]), the deviation between the two is 35.7δ[(MPa) 1 / 2 ](See Figure 4 ). The deviation of the Hansen solubility parameters of water and acetone relative to PDLLGA is significantly greater than the deviation of ethanol and acetone relative to PDLLGA. As a result, the spinning solution extruded from the nozzle solidifies rapidly in water. Therefore, if the ejection speed and solidification are not balanced, it will often solidify at the front end of the nozzle before fiberization and cannot be ejected and thus cannot be fiberized, making it difficult to fiberize stably. On the other hand, the specific gravity of water is much greater than that of acetone, so the acetone dissolved from the spinning solution will not be stored at the bottom of the container, but will float to the vicinity of the upper surface. When good conditions are selected for spinning, the fibers will not be stuck together again by acetone, and long continuous fibers can be formed. The inventors of the present invention have given deep thought to the above phenomenon and continued to conduct in-depth research, and have completed a new wet spinning method that can stably spin filaments and the resulting fibers are independent of each other and become soft cotton-like. In this method, the spinning solution is injected into a poor solvent with a small deviation of the Hansen solubility parameter from the good solvent, and then it is allowed to enter the poor solvent with a larger deviation than the former in a state where it has not yet been completely solidified to be solidified.

[0054] Example 1 (using ethanol / water as poor solvent) The materials and apparatus shown below were used. β-tricalcium phosphate (Ca 3 (PO 4 ) 2 ): Taihei Chemical Industry Co., Ltd. β-TPP-100. The material (β-TCP crushed product) obtained by crushing particles with a particle size of 1.7 mm or less to about 4 μm was used. PDLLA:PGA (75:25): PURASORB PDLG 7507, Corbion Purac were used as PDLLGA. ·Ethanol: Kishida Chemical, first-grade purity 99.5% ·Acetone: Wako Pure Chemical Industries, Ltd. reagent, special grade, purity 99.5+% Water: Purified water ·Injection nozzle for spinning fluid: Termo injection needle 27G (inner diameter 0.2mm, outer diameter 0.4mm) Place the cylindrical collection container (see Figure 1 ) After filling it to a certain height with distilled water, slowly pour in ethanol. The specific gravity of ethanol is 789kg / m 3 (20°C), is smaller than water, so if left to stand, water and ethanol will not mix.

[0055] 1. Preparation of spinning solution β-TCP and PDLLGA were mixed at a weight ratio of 7:3 and dissolved in acetone and mixed overnight to prepare a spinning solution with a polymer concentration of 20%. 2. Spinning conditions The incident needle of the wet spinning device (Termo injection needle 27G) was set in the vertical downward direction in the collection container, and extruded into the ethanol in the collection container at an extrusion rate of 3 ml / h. 3. Fibration of spinning solution i) The spinning solution extruded from the spinning tube is injected into the ethanol in the collecting container in the form of fibers without causing clogging at the nozzle outlet. ii) The fibrous spinning solution injected into the ethanol solidifies on its surface and is injected into the water below the ethanol filling the collection container before the acetone is completely released from the inside, and is stored at the bottom of the collection container through the water (see Figure 2 ). 4. Recovery of cotton wool The fibers floating and deposited at the bottom of the collection container were washed with water and kept overnight to remove the solvent. The water was then removed with an absorbent sheet and dried at room temperature to obtain a cotton-like sample. 5. Fiber properties of the obtained samples i) The diameter of the fiber is about 130 μm, and the cross section of the fiber is approximately elliptical. ii) β-TCP particles are exposed on the surface of the fiber to form a concave-convex shape (see Figure 3 ). The inventors immersed the sample in hydrochloric acid to confirm whether the β-TCP particles exposed on the fiber surface were covered by the resin layer (if the β-TCP particles on the fiber surface were covered by the resin layer, the β-TCP particles would not be dissolved by hydrochloric acid). The results showed that the β-TCP particles exposed on the fiber surface of the sample were not covered by the resin layer.

[0056] Example 2 (using a mixture of acetone and water / water as a poor solvent) The materials and apparatus shown below were used. β-tricalcium phosphate (Ca 3 (PO 4 ) 2 ): Taihei Chemical Industry Co., Ltd. β-TPP-100. The material used was a material obtained by crushing particles with a particle size of 1.7 mm or less into particles of about 4 μm (β-TCP crushed product). PDLLA:PLGA (75:25) (PURASORB PDLG 7507, Corbion Purac) was used as PDLLGA. Distilled water ·Acetone: Wako Pure Chemical Industries, Ltd. reagent, special grade, purity 99.5+% Acetone and water were mixed at a weight ratio of 8:2 and stirred thoroughly to prepare the first poor solvent. ·Injection nozzle for spinning fluid: Termo injection needle 27G (inner diameter 0.2mm, outer diameter 0.4mm) · First poor solvent (mixed solvent of acetone:water=8:2) container: a cylinder with a diameter of 15 mm and a height of 50 mm was used. Second poor solvent (water) container: A cylindrical container with a diameter of 90 mm and a height of 300 mm was used. The first poor solvent container (cylindrical) and the second poor solvent container (cylindrical) were fixed with a clamp. After filling the second poor solvent container with distilled water, slowly pour the mixed solvent of acetone and water into the first poor solvent container. Due to the difference in specific gravity, the water and the mixed solvent will not mix if left to stand.

[0057] 1. Preparation of spinning solution β-TCP and PDLLGA were mixed in a weight ratio of 7:3 and dissolved in acetone, and mixed overnight to prepare a spinning solution with a polymer concentration of 20%. 2. Spinning conditions The injection needle (caliber 27G) was set vertically downward, and the solution was extruded into the first poor solvent (acetone and water) at an extrusion rate of 3 ml / h. 3. Fibration of spinning solution i) The spinning solution extruded from the spinning tube is incident into the first poor solvent (acetone and water) in the collecting container in the form of fibers without solidifying at the outlet of the nozzle to cause clogging. ii) The fibrous spinning stock solution injected into the first poor solvent (acetone and water) solidifies on its surface and is injected into the second poor solvent (water) filling the lower part of the collection container before the acetone is completely released from the inside, and is stored at the bottom of the collection container through the water (see Figure 2 ). 4. Recovery of cotton wool The solvent acetone in the spinning solution is exchanged with the low-concentration water in the first poor solvent (mixed solution of acetone and water). The spinning solution solidifies on its surface, but flows out smoothly without solidifying at the front end of the nozzle. Before it is completely exchanged inside, it contacts the water of the second poor solvent and is stored at the bottom of the container. Since the specific gravity of acetone is smaller than that of water, it will not be stored at the bottom of the container, but will float to the vicinity of the upper surface. As a result, even if the spinning is done for a long time, the fibers will not be stuck together again by acetone, and long fibers can be obtained. After wet spinning, the fibers are taken out and dried on an absorbent sheet at room temperature to obtain a cotton-like sample. 5. Fiber properties of the obtained samples i) The diameter of the fiber is about 110 μm, and the cross section of the fiber is approximately circular. ii) β-TCP particles are exposed on the surface of the fiber to form an uneven shape. The inventors immersed the sample in hydrochloric acid to confirm whether the β-TCP particles exposed on the fiber surface were covered by the resin layer (if the β-TCP particles on the fiber surface were covered by the resin layer, the β-TCP particles would not be dissolved by hydrochloric acid). The results showed that the β-TCP particles exposed on the fiber surface of the sample were not covered by the resin layer.

[0058] Comparative experiment 1 (ethanol 100%) Experimental contents: Under the same conditions as in Example 1, a spinning experiment was carried out by filling the collection container with only ethanol as the poor solvent. Results: The spinning solution filled in the spinning tube could be smoothly extruded from the nozzle outlet (27G) in the form of fibers. However, the fibers could not maintain their shape in ethanol and were frequently torn.

[0059] Comparative experiment 2 (water 100%) Experimental contents: Under the same conditions as in Example 1, a spinning experiment was carried out by filling the collection container with only water as the poor solvent. Results: The spinning solution filled in the spinning tube was frequently clogged at the nozzle outlet (27G) and could not be injected into the water.

[0060] The present invention has been described above using an example in which the spinning solution contains inorganic filler particles. However, the wet spinning method using two poor solvents of the present invention is not limited to the production of cotton-like products, but can also be used as a method for producing nonwoven fabrics.

Claims

1. A method for producing biodegradable fibers containing inorganic filler particles by wet spinning, wherein: A mixture of inorganic filler particles and biodegradable resin in a weight ratio of 50-80:50-20 is placed in a mixing container. A good solvent having a predetermined amount relative to the mixture is added to the mixing container, and the biodegradable resin is dissolved in the good solvent and stirred, thereby preparing a spinning solution in which the inorganic filler particles are dispersed in the solution. The prepared spinning solution is filled into the spinning tube of the wet spinning device, The spinning solution filled in the spinning tube is extruded vertically downward from a nozzle of an incident needle having a specified diameter at a specified extrusion speed and ejected into a cylindrical collection container having a specified height, wherein the collection container is filled with a first poor solvent having a solubility parameter value with a first deviation relative to the good solvent and a second poor solvent having a specific gravity greater than that of the first poor solvent and a solubility parameter value with a second deviation greater than the first deviation relative to the good solvent, filling upper and lower layers, The spinning stock solution extruded from the nozzle outlet is incident into the first poor solvent in the collecting container in the form of fibers by its own weight, and the surface of the spinning stock solution incident into the liquid of the first poor solvent in the form of fibers is solidified by mutual diffusion of the detachment of the good solvent and the intrusion of the first poor solvent. Then, the surface-solidified fibrous spinning solution is continuously injected into the second poor solvent below the first poor solvent filling the collection container by its own weight. The fibrous spinning solution injected into the second poor solvent is further solidified and fiberized in the second poor solvent by mutual diffusion of the detachment of the good solvent and the intrusion of the second poor solvent into the interior of the spinning solution. The solidified fibers become continuous long fibers that are not bonded to each other in the second poor solvent and float and accumulate at the bottom of the collection container. The fibers accumulated at the bottom of the collection container are taken out from the collection container and dried.

2. The method of claim 1, wherein: The biodegradable resin is PDLLGA, the good solvent is acetone, the first poor solvent is ethanol, and the second poor solvent is water. 3 . The method according to claim 1 , wherein the biodegradable resin is PDLLGA, the good solvent is acetone, the first poor solvent is a mixed solution of acetone and water, and the second poor solvent is water.

4. The method according to claim 1 or 2, wherein: The amount of the good solvent added to the mixture of the inorganic filler particles and the biodegradable resin is adjusted to an amount in which the inorganic filler particles are uniformly dispersed in the solution without settling in the spinning tube and can be fiberized in the poor solvent by extruding the spinning solution from the incident needle into the poor solvent.

5. The method according to claim 1 or 2, wherein: The outer diameter of the fibers taken out from the collection container and dried is 80 to 200 μm.

6. The method according to claim 1 or 2, wherein: The diameter of the jet outlet of the incident needle was 0.17 to 0.21 mm (27G), and the outer diameter of the fiber taken out from the collection container and dried was 100 to 150 μm.

7. The method according to claim 1 or 2, wherein: The inorganic filler particles are calcium salt particles.

8. A cotton-like bone regeneration material produced by wet spinning, wherein: The cotton-like bone regeneration material is manufactured by the following steps: A mixture of calcium salt particles and biodegradable resin in a weight ratio of 50-80:50-20 is placed in a mixing container. A good solvent having a predetermined amount relative to the mixture is added to the mixing container, and the biodegradable resin is dissolved in the good solvent and stirred, thereby preparing a spinning solution in which the calcium salt particles are dispersed in the solution. The prepared spinning solution is filled into the spinning tube of the wet spinning device, The spinning solution filled in the spinning tube is extruded vertically downward from a nozzle of an incident needle having a specified diameter at a specified extrusion speed and ejected into a cylindrical collection container having a specified height, wherein the collection container is filled with a first poor solvent having a solubility parameter value with a first deviation relative to the good solvent and a second poor solvent having a specific gravity greater than that of the first poor solvent and a solubility parameter value with a second deviation greater than the first deviation relative to the good solvent, filling upper and lower layers, The spinning stock solution extruded from the nozzle is incident in the first poor solvent in the collecting container in the form of fibers, and the surface of the spinning stock solution incident in the first poor solvent liquid in the form of fibers is solidified by mutual diffusion of the detachment of the good solvent and the intrusion of the first poor solvent. Next, the surface-solidified fibrous spinning solution is continuously injected into the second poor solvent below the first poor solvent filling the collection container. The fibrous spinning solution injected into the second poor solvent is further solidified and fiberized in the second poor solvent by mutual diffusion of the detachment of the good solvent and the intrusion of the second poor solvent into the interior of the spinning solution. The solidified fibers become continuous long fibers that are not bonded to each other in the second poor solvent and float and accumulate at the bottom of the collection container. The fibers accumulated at the bottom of the collection container are taken out from the collection container and dried.

9. The bone regeneration material according to claim 8, wherein: The biodegradable resin is PDLLGA, the good solvent is acetone, the first poor solvent is ethanol, and the second poor solvent is water.

10. The bone regeneration material according to claim 8, wherein The biodegradable resin is PDLLGA, the good solvent is acetone, the first poor solvent is a mixed solution of acetone and water, and the second poor solvent is water.

11. The bone regeneration material according to claim 8 or 9, wherein: The amount of the good solvent added to the mixture of the inorganic filler particles and the biodegradable resin is adjusted to an amount in which the inorganic filler particles are uniformly dispersed in the solution without settling in the spinning tube and can be fiberized in the poor solvent by extruding the spinning solution from the incident needle into the poor solvent.

12. A wet spinning apparatus for an improved wet spinning process, wherein: The device comprises: A spinning tube into which a spinning solution is injected, wherein the spinning solution is prepared by adding 50-80 wt % of inorganic filler particles and 50-20 wt % of biodegradable resin into a mixing container, dissolving them in a good solvent and stirring them, a nozzle connected to the end of the spinning tube and having a spray outlet at the front end, and A cylindrical collecting container having a specified height; The collection container comprises: an injection section for injecting the spinning solution extruded from the nozzle outlet into the first poor solvent and passing the first poor solvent, a fiber solidification section adjacent to the ejection section, which allows the spinning solution passing through the ejection section to be injected into a second poor solvent having a larger specific gravity than the first poor solvent and a larger deviation of the solubility parameter value from the good solvent than the first poor solvent to be solidified; The fiber recovery section is adjacent to the fiber solidification section and is used to collect the solidified fibers passing through the fiber solidification section in the form of cotton wool and then float on the bottom of the collection container. The fiber solidification section and the fiber recovery section are connected in a detachable manner. After the solidified fibers float and accumulate at the bottom of the fiber recovery section, the fiber recovery section is separated from the fiber solidification section, thereby being able to recover the fibers accumulated at the bottom of the collection container.

13. The wet spinning apparatus according to claim 12, wherein: The biodegradable resin is PDLLGA, the good solvent is acetone, the first poor solvent is ethanol, and the second poor solvent is water.

14. The wet spinning apparatus according to claim 12, wherein: The biodegradable resin is PDLLGA, the good solvent is acetone, the first poor solvent is a mixed solution of acetone and water, and the second poor solvent is water.

Citation Information

Patent Citations

  • Spin bath and method for consolidation of a shaped article

    CN104838048A

  • Method for preparing cellulose fibers by dry-wet spinning

    CN106048741A

  • Method for manufacturing bone-regeneration material comprising biodegradable fibers by using electrospinning method

    CN108289975A

  • Improvements relating to the manufacture of artificial threads

    GB347878A

  • Method for spinning synthetic fibers

    JP2009221642A